Potentiometric determination of captopril in pharmaceutical formulations - Ribeiro,P. R. da S. (2003)
A simple, precise, rapid and low-cost potentiometric method for captopril determination in pure form and in pharmaceutical preparations is proposed. Captopril present in tablets containing known quantity of drug was potentiometrically titrated in aqueous solution with NaOH using a glass pH electrode, coupled to an autotitrator. No interferences were observed in the presence of common components of the tablets as lactose, microcrystalline cellulose, croscarmellose sodium, starch and magnesium stearate. The analytical results obtained by applying the proposed method compared very favorably with those obtained by the United States Pharmacopoeia Standard procedure. Recovery of captopril from various tablet dosage formulations range from 98.0 to 102.0%.